PENGARUH INTERVENSI KEPERAWATAN BERBASIS MODEL KONSEPTUAL LEVINE TERHADAP KECEMASAN PADA PASIEN FRAKTUR - Henrianto Karolus Siregar; Dudut Tanjung; Nunung Febriany Sitepu (Jurnal Ilmu Keperawatan Medikal Bedah, 2020)
Fracture is the discontinuity of bone tissues according to their types and areas. Intervention for recovering fractured patients is done by using Levine theory. The objective of the research was to identify the influence of Levine conceptual model based-intervention on anxiety. The research used quasi-experimental method with equivalent control group design. The samples were 52 respondents, 26 of them were in the intervention group ad the other 26 of them were in the control group, taken by using consecutive sampling technique. The data were analyzed by using paired t-test and independent t-test. The result of the research showed that there the influence of Levine conceptual model based-intervention program on anxiety before and after the intervention at p-value=0.000 (p<0.05). There was the difference of this type of intervention from hospital standard nursing intervention at p-value = 0.000 (p<0.5). The conclusion that there was the influence of Levine conceptual model based-intervention program on anxiety. It is recommended that this type of nursing intervention be used as a part of independent nursing intervention to help handle on anxiety of fractured patients.